2010
DOI: 10.2528/pier09091706
|View full text |Cite
|
Sign up to set email alerts
|

Microwave Measurements of Dielectric Constants by Exponential and Logarithmic Mixture Equations

Abstract: Abstract-This article reports on a study of the dielectric constants of ceramic dispersions in the polyethylene matrix at microwave frequency. The exponential and logarithmic mixture rules are studied in three ceramic powders of fillers with dielectric constants 10, 20, and 36, respectively. The experimental values of the dielectric constants of the mixtures are compared to those obtained by using different mixing laws. The mixing rules are also adopted to calculate the dielectric constants of pure ceramics fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 24 publications
1
13
0
Order By: Relevance
“…Conversely, the Lichtenecker Rother equation again conforms well to the form of the experimental data set (R 2 = 0.998), albeit that, in this case, the derived permittivity value of BaTiO 3 is lower than anticipated, at 520 ± 70. This result is, perhaps, less surprising than the very reasonable permittivity value determined for the PZT above, since it has been reported that, in general, effective medium theories do not conform to experiment across the complete composition range [8]. …”
Section: Permittivity and Composition Of Batio 3 -Based Compositessupporting
confidence: 50%
“…Conversely, the Lichtenecker Rother equation again conforms well to the form of the experimental data set (R 2 = 0.998), albeit that, in this case, the derived permittivity value of BaTiO 3 is lower than anticipated, at 520 ± 70. This result is, perhaps, less surprising than the very reasonable permittivity value determined for the PZT above, since it has been reported that, in general, effective medium theories do not conform to experiment across the complete composition range [8]. …”
Section: Permittivity and Composition Of Batio 3 -Based Compositessupporting
confidence: 50%
“…To do this, the analysis method and theoretical accuracy on six basic mixture laws derived from three basic particle shapes of ceramic fillers has been reported for dielectric constants of ceramic less than 40 at microwave frequency [22]. Similar researches have been done for other well known mixture rules [23]. They have shown that both the physical curve matching with experimental results and low potential theory error are important to promote the calculation accuracy.…”
Section: Introductionmentioning
confidence: 93%
“…Various mixture equations have been proposed in the past to determine the effective complex permittivity of mixed dielectrics, and one of the generalized forms for the twophase mixture can be given by the Maxwell Garnett formula [6,9] [20][21][22][23][24] formulations for the two-phase media, which might provide improved values under certain conditions. However, most of these equations usually provide good results for powdered shaped materials where they can be assumed to be mixed homogenously.…”
Section: Proposed Mixing Formula For Slab Shaped Samples In Rectangulmentioning
confidence: 99%